Effectiveness of Structured Coping Strategies in Reducing Perceived Postpartum Stress Among Postnatal Mothers in selected settings - Mrs. Rosy. P; Mrs. K. Bindhu; Mrs. Gayathri. T; Mrs. R. Yuvashree; Ms. B. Kaviya; Ms. B. Kavikuilrani; Mrs. Aleena Meety Lal. A (The Bioscan, 2024)
Background of the study: The postpartum period brings significant changes, often causing stress and anxiety in mothers, impacting maternal health, infant development, and family dynamics. This study evaluates the effectiveness of structured coping strategies, like problem solving and social support, in reducing postpartum stress, promoting improved mental health and family well-being. Aim: To assess the effectiveness of structured coping strategies in reducing perceived postpartum stress among postnatal mothers. Results: The pretest and posttest results show a significant reduction in perceived postpartum stress after the intervention. Initially, only 1.67% of participants reported low stress, rising to 62.67% post-intervention. Moderate stress dropped from 68.33% to 30.66%, and high stress decreased from 30% to 6.67%. Coping strategies improved, with the problem-focused coping mean increasing from 2.0 to 4.1 and emotion-focused coping rising from 1.5 to 3.5, both showing significant improvement (t-value = 2.66, p-value = 0.005, df = 59). These findings highlight the intervention's effectiveness, emphasizing the need for enhanced support for postpartum mothers. Conclusion: This study demonstrates that structured coping strategies effectively reduce postpartum stress, with most mothers transitioning from moderate or high to low stress post-intervention. Significant associations with demographic factors highlight the importance of personalized support. Enhanced problem- and emotion-focused coping mechanisms emphasize the need for ongoing mental health support for new mothers.